Perovskite tungstate Ba2La2ZnW2O12:Mn4+ phosphor: Synthesis, energy transfer and tunable emission. (May 2021) - Cao, Renping; Zhang, Weijun; Chen, Ting; Zheng, Yunfei; Ao, Hui; Luo, Zhiyang; Xie, Shikun; Wan, Huijun
Graphical abstract: Highlights: Novel Ba2 La2 ZnW2 O12 :Mn 4+ phosphor is prepared by the solid-state reaction method in air. Ba2 La2 ZnW2 O12 :xMn 4+ phosphors show an adjustable photo-luminescence characteristic. The luminous mechanism is explained by the Tanabe Sugano energy level diagram of Mn 4+ ion. Abstract: Ba2 La2 ZnW2 O12 :xMn 4+ (BLZWO:xMn 4+ ) (0 ≤ x ≤ 1.2 mol%) are prepared via the solid state reaction method under air conditions. The crystal phases and optical properties of all samples are investigated. The yellow emission of BLZWO is observed with the chromaticity coordinates (0.3940, 0.4389), and its emission spectrum covers the region from 380 to 810 nm owing to the W 6+ - O 2− transition. When the excitation wavelength is 344 nm, BLZWO:xMn 4+ show an adjustable photo-luminescence characteristic by altering the Mn 4+ concentration owing to the energy transfer from [WO6 ] group to Mn 4+ ions. With excitation at 514 nm, BLZWO:xMn 4+ only show red emission. The excitation spectrum of BLZWO:Mn 4+ with peaks at 344 and 514 nm is in the region from 210 to 600 nm and its emission spectrum with peak at 704 nm are observed in the range of 625–800 nm. The lifetimes of BLZWO:xMn 4+ reduce successively with adding Mn 4+ concentration. The results are good for the basic research on luminescence characteristics of Mn 4+ ion.